A cobalt-doped hydroxyapatite catalyst, a preparation method and application thereof

CN122875261APending Publication Date: 2026-10-09TIANJIN NANKAI HOSPITAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611130313.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

本发明通过将Co2+离子掺杂进入羟基磷灰石晶格中的Ca2+位点,利用晶格掺杂态Co2+对PMS分子活化路径的定向调控作用,实现PMS活化过程中·OH的高选择性生成,有效解决现有PMS活化催化剂自由基选择性差和生物相容性不足的双重技术问题

Benefits of technology

[0024]本发明通过将Co2+离子掺杂进入羟基磷灰石晶格中的Ca2+位点,利用晶格掺杂态Co2+对PMS分子活化路径的定向调控作用,实现PMS活化过程中·OH的高选择性生成,有效解决现有PMS活化催化剂自由基选择性差和生物相容性不足的双重技术问题。同时,以具有临床成熟应用基础的羟基磷灰石为基体,赋予该催化材料良好的生物相容性和安全性基础,为其在生物医学相关的高级氧化应用提供技术支撑。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875261A_ABST
    Figure CN122875261A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of biological medical catalytic materials, and particularly discloses a cobalt-doped hydroxyapatite catalyst as well as a preparation method and application thereof. 2+ The application takes human natural bone component hydroxyapatite as a matrix, replaces Co into the Ca site of HAP crystal lattices through a co-precipitation calcination process, and obtains a crystal lattice doped Co-HAP catalyst. The catalyst can directionally regulate the PMS activation path, highly selectively generates hydroxyl radicals (·OH), and greatly inhibits byproducts such as sulfate radicals and superoxide anions. Meanwhile, the HAP matrix endows the material with excellent biocompatibility, and the crystal lattice bonded cobalt ion dissolution amount is extremely low, and the crystal and micro-morphology remain stable after recycling. The material can be used for an antibacterial coating of an orthopedic implant, an infected bone repair bracket, and surface disinfection of medical devices, and has both local precise oxidation antibacterial and bone induction repair dual functions, and solves the industry bottlenecks of poor biological toxicity and poor free radical selectivity of traditional industrial catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical catalytic materials technology, and relates to a cobalt-doped hydroxyapatite catalyst, its preparation method and application, specifically a cobalt-doped hydroxyapatite catalyst that selectively generates hydroxyl radicals and its application in activating peroxymonosulfate, and is particularly suitable for applications related to oxidative stress in medical device surface treatment and implants. Background Technology

[0002] Persulfate (PMS) activation of advanced oxidation processes has attracted widespread attention in the fields of organic pollutant degradation and microbial inactivation due to its advantages such as simple operation, mild reaction conditions, and strong oxidizing power. The PMS molecule contains a peroxy bond (OO), and the mode of peroxy bond breaking during catalytic activation determines the types of reactive oxygen species generated. Specifically, homolytic cleavage of the OO bond in the PMS molecule tends to generate sulfate radicals (·SO4). - The breaking of the OH bond tends to generate hydroxyl radicals (·OH). Hydroxyl radicals are among the most potent reactive oxygen species known, with an oxidation potential as high as 2.8 V and a reaction rate constant generally in the range of 10⁻⁶. 8 ~10 10 M -1 s -1 The oxidation process is on the order of magnitude larger and its oxidation is non-selective, capable of indiscriminately attacking key structures of bacteria such as cell walls, cell membranes, proteins, and nucleic acids. Compared to traditional antibacterial strategies that rely on specific targets, the ·OH-based oxidation process is less likely to induce microbial resistance and has broad-spectrum and highly effective application potential.

[0003] However, existing PMS-activated catalysts generally face the following technical problems during the activation process:

[0004] (1) Poor selectivity in free radical generation. Most existing catalysts (including transition metal ions, metal oxides, carbon-based materials, and MOF-derived materials) tend to generate both ·OH and ·SO4 simultaneously when activating PMS. - Superoxide anion radicals (·O2) - ) and singlet oxygen ( 1 Various active species, including O2, exist. The oxidation potential and reaction selectivity of different active species vary significantly. The coexistence of multiple species not only disperses the oxidation capacity but also reduces the overall oxidation efficiency due to mutual quenching between different free radicals, while increasing the probability of side reactions. Achieving highly selective ·OH generation during PMS activation is one of the core challenges in the research of advanced oxidation catalytic materials.

[0005] (2) Insufficient biocompatibility of existing catalytic materials. Currently reported highly efficient PMS-activated catalysts are mostly based on transition metal oxides (such as Co3O4, Fe2O3, MnO2), carbon-based materials (such as graphene oxide, nitrogen-doped carbon), or metal-organic framework (MOF) derivatives. The composition and structural design of these materials are mainly geared towards industrial wastewater treatment scenarios, lacking consideration for safety and compatibility with the human body and environment. When these materials are applied to biomedical oxidation processes, there are potential risks such as metal ion leaching toxicity, particulate matter residue, and inflammatory reactions, making it difficult to meet the basic safety requirements for in vivo or external application. This biocompatibility bottleneck severely limits the expansion of PMS-activated advanced oxidation technology in the biomedical field.

[0006] Hydroxyapatite [HAP, Ca] 10 [(PO4)6(OH)2] is a major inorganic component of human bone tissue and tooth enamel, possessing excellent biocompatibility, osteoconductivity, and ion exchange capacity. It has been widely approved by the US FDA and China NMPA for use in orthopedic implant coatings, bone defect repair scaffolds, and artificial bone substitutes. The lattice structure of HAP exhibits unique ion-substitutable properties, and its Ca... 2+ The site can accommodate a variety of transition metal ions (such as Co). 2+ Fe 3+ Cu 2+ (e.g., metal ions) enter the crystal lattice through ion replacement, and the replaced metal ions are chemically bonded and dissolved in the crystal lattice, resulting in a lower risk of ion dissolution compared to surface-supported catalytic materials. This structural feature endows HAP with unique potential as a matrix for biomedical PMS catalytic materials.

[0007] Existing studies have explored the application of HAP as a catalytic material support, such as loading nickel magnetite (NiFe3O4) onto the surface of HAP for the degradation of the micro-pollutant sulfamethoxazole. However, these studies still have the following shortcomings: (1) The active components exist in the form of surface physical loading rather than lattice doping, resulting in weak interaction between the active material and the support. Aggregation and shedding are prone to occur during long-term use, leading to catalytic activity decay and increased metal ion dissolution; (2) The traditional PMS activation pathway is still used, failing to solve the problem of selective regulation of free radical generation, ·OH, ·SO4 - O2 - and 1 The problem of multiple free radicals, such as O2, coexisting still exists.

[0008] In summary, there is an urgent need to develop a PMS-activated catalytic material that combines biocompatibility and ·OH selectivity to overcome the bottlenecks of existing catalytic materials in advanced biomedical oxidation applications. Summary of the Invention

[0009] To address the shortcomings of existing technologies, this invention provides a cobalt-doped hydroxyapatite catalyst for selectively generating hydroxyl radicals, its preparation method, and its applications. This invention utilizes Co... 2+ Ca ions are incorporated into the hydroxyapatite lattice. 2+ Sites, utilizing lattice-doped Co 2+ This method enables targeted regulation of the PMS molecular activation pathway, achieving highly selective generation of ·OH during PMS activation and effectively addressing the dual technical challenges of poor radical selectivity and insufficient biocompatibility in existing PMS activation catalysts. Furthermore, using hydroxyapatite, a material with proven clinical applications, as a matrix endows the catalytic material with excellent biocompatibility and safety, providing technical support for its advanced oxidation applications in biomedicine.

[0010] The first objective of this invention is to provide a method for preparing a cobalt-doped hydroxyapatite catalyst, comprising the following steps:

[0011] S1: Preparation of calcium salt solution

[0012] Calcium nitrate tetrahydrate is dissolved in deionized water, and cobalt chloride hexahydrate is added and mixed to obtain a calcium-cobalt mixed salt solution; diammonium hydrogen phosphate aqueous solution is prepared; S2: the pH of the calcium-cobalt mixed salt solution is adjusted to 10-11 using ammonium hydroxide; S3: under stirring conditions, diammonium hydrogen phosphate aqueous solution is added dropwise to the system obtained in step S2, controlling the Ca / P molar ratio to 1.67, to obtain a reaction suspension; S4: the suspension is placed in a 90 ℃ water bath for stirring and crystallization for 2 h, and aged at room temperature for 12 h; S5: the aged mixture is filtered, washed, dried at 100 ℃, and ground into powder; S6: the powder is placed in a muffle furnace, heated to 500 ℃ at 2 ℃ / min and calcined for 5 h, cooled, washed with water, and dried to obtain the Co-HAP catalyst.

[0013] Preferably, step S1 specifically involves: weighing 1.19 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and dissolving it in 100 mL of deionized water, then sonicating until the solid is completely dissolved to obtain a calcium nitrate solution; subsequently, weighing cobalt chloride hexahydrate according to the target doping stoichiometric ratio and adding it to the calcium nitrate solution, stirring until completely dissolved to obtain a calcium-cobalt mixed salt solution; and separately weighing 0.4 g of diammonium hydrogen phosphate and dissolving it in 100 mL of deionized water, then sonicating until the solid is completely dissolved to obtain a diammonium hydrogen phosphate solution.

[0014] Preferably, step S2 specifically involves adding 0.025 mol·mL⁻¹ dropwise to the calcium-cobalt mixed salt solution. -1 Ammonium hydroxide solution, adjust the pH of the system to 10-11.

[0015] Preferably, step S3 specifically involves: setting the stirring speed to 400 rpm, and under continuous stirring, adding 100 mL of the diammonium hydrogen phosphate solution dropwise to the system obtained in step S2, adjusting the raw material Ca / P molar ratio to 1.67, and obtaining a reaction suspension after the addition is complete.

[0016] Preferably, step S4 specifically involves: placing the suspension in a 90°C water bath and continuously stirring at a constant temperature for 2 hours, then turning off the heating and stirring devices and allowing it to age at room temperature for 12 hours.

[0017] Preferably, step S5 specifically involves: filtering and washing the aged mixture, drying the filter cake in an electric oven at 100°C, and then grinding the dried solid into powder.

[0018] Preferably, step S6 specifically involves: placing the powder in a muffle furnace, heating it to 500°C at a heating rate of 2°C / min, and calcining it at a constant temperature for 5 hours; after cooling the calcined product, filtering and washing it again, and drying the resulting solid at 80°C to finally obtain the Co-HAP catalyst.

[0019] Using the above technical solution, Co 2+ It enters the Ca sites of the HAP lattice through ion replacement; during PMS activation, the OH bonds of the PMS molecule are directionally broken, inhibiting homolytic cracking of OO and significantly reducing SO42-. - O2 - The formation of ·OH enables highly selective production; at the same time, the lattice chemical bonds bind cobalt ions, greatly reducing the toxicity of metal leaching, and the HAP matrix ensures the biocompatibility and osseointegration ability of the material.

[0020] A second objective of this invention is to provide a cobalt-doped hydroxyapatite catalyst prepared by the above method, using hydroxyapatite Ca... 10 (PO4)6(OH)2 is the matrix, Co 2+ Ca is replaced by lattice ion substitution. 2+ Uniform doping at each site, with a cobalt doping amount of 2%-10%.

[0021] A third objective of this invention is to provide the application of the above-mentioned cobalt-doped hydroxyapatite catalyst in the selective generation of hydroxyl radicals by activating PMS.

[0022] Preferred applications include antibacterial coatings on orthopedic implants, scaffolds for repairing infected bone defects, and oxidative sterilization of medical device surfaces.

[0023] The beneficial effects of this invention are:

[0024] This invention uses Co 2+ Ca ions are incorporated into the hydroxyapatite lattice. 2+ Sites, utilizing lattice-doped Co2+ This method enables targeted regulation of the PMS molecular activation pathway, achieving highly selective generation of ·OH during PMS activation and effectively addressing the dual technical challenges of poor radical selectivity and insufficient biocompatibility in existing PMS activation catalysts. Furthermore, using hydroxyapatite, a material with proven clinical applications, as a matrix endows the catalytic material with excellent biocompatibility and safety, providing technical support for its advanced oxidation applications in biomedicine. Attached Figure Description

[0025] Figure 1 The XRD diffraction patterns are shown for pure HAP and HAP samples with different Co doping ratios.

[0026] Figure 2 The images show the FTIR infrared spectra of pure HAP and HAP samples with different Co doping ratios.

[0027] Figure 3 The figures show the XPS spectra of pure HAP and the Co-HAP sample prepared in Example 1. Figure (a) is the full spectrum, Figure (b) is the high-resolution Co 2p spectrum, Figure (c) is the high-resolution P 2p spectrum, Figure (d) is the high-resolution O 1s spectrum, and Figure (e) is the high-resolution Ca 2p spectrum.

[0028] Figure 4 SEM microstructure images (a, b) of pure HAP and Co-HAP samples prepared in Example 1, and EDS elemental distribution map (c) of Co-HAP.

[0029] Figure 5 The graph shows the change in hydroxyl radical (·OH) concentration with reaction time in HAP systems with different Co doping ratios.

[0030] Figure 6 Superoxide radicals (·O2) in HAP systems with different Co doping ratios - Concentration changes over reaction time.

[0031] Figure 7 Quantification of sulfate radicals (·SO4) using benzoic acid probe method 2- Characteristic substrate residual concentration curve.

[0032] Figure 8 A comparison of the normalized ratio activities of PMS for generating hydroxyl radicals (·OH) by different catalysts.

[0033] Figure 9Comparison of crystal structure and chemical bond energy spectrum of Co-HAP catalyst prepared in Example 1 of the present invention before and after reaction: (a) XRD diffraction pattern of Co-HAP catalyst before and after PMS activation reaction; (b) FTIR infrared spectrum of Co-HAP catalyst before and after PMS activation reaction.

[0034] Figure 10 The image shows the SEM image of the microstructure of the Co-HAP catalyst after the reaction. Detailed Implementation

[0035] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.

[0036] Example 1

[0037] A method for preparing a cobalt-doped hydroxyapatite catalyst includes the following steps:

[0038] S1: Preparation of calcium salt solution

[0039] Weigh 1.19 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and dissolve it in 100 mL of deionized water. Sonicate until the solid is completely dissolved to obtain a calcium nitrate solution. Then, weigh cobalt chloride hexahydrate according to the target doping ratio and add it to the calcium nitrate solution. Stir until completely dissolved to obtain a calcium-cobalt mixed salt solution. Separately, weigh 0.4 g of diammonium hydrogen phosphate and dissolve it in 100 mL of deionized water. Sonicate until the solid is completely dissolved to obtain a diammonium hydrogen phosphate solution. S2: Add 0.025 mol·mL⁻¹ dropwise to the calcium-cobalt mixed salt solution. -1 Ammonium hydroxide solution was used to adjust the pH of the system to 10-11. S3: The stirring speed was set to 400 rpm. Under continuous stirring, 100 mL of the diammonium hydrogen phosphate solution was added dropwise to the system obtained in step S2, adjusting the Ca / P molar ratio of the raw materials to 1.67. After the addition was complete, a reaction suspension was obtained. S4: The suspension was placed in a 90 ℃ water bath and stirred continuously at a constant temperature for 2 h. Then, the heating and stirring devices were turned off, and the mixture was allowed to age at room temperature for 12 h. S5: The aged mixture was filtered and washed with water. The filter cake was dried in an electric oven at 100 ℃. After drying, the solid was thoroughly ground into powder. S6: The powder was placed in a muffle furnace and heated to 500 ℃ at a rate of 2 ℃ / min, and calcined at a constant temperature for 5 h. After cooling, the calcined product was filtered and washed again. The resulting solid was dried at 80 ℃ to finally obtain the Co-HAP catalyst.

[0040] In this embodiment, the cobalt doping level is 6%.

[0041] Example 2

[0042] The difference from Example 1 is that the cobalt doping amount is 2%.

[0043] Example 3

[0044] The difference from Example 1 is that the cobalt doping amount is 4%.

[0045] Example 4

[0046] The difference from Example 1 is that the cobalt doping level is 8%.

[0047] Example 5

[0048] The difference from Example 1 is that the cobalt doping amount is 10%.

[0049] Comparative Example 1

[0050] A method for preparing a hydroxyapatite (HAP) catalyst includes the following steps:

[0051] T1: Weigh 1.19 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and dissolve it in 100 mL of deionized water. Sonicate until the solid is completely dissolved to obtain a calcium nitrate solution. Separately, weigh 0.4 g of diammonium hydrogen phosphate and dissolve it in 100 mL of deionized water. Sonicate until the solid is completely dissolved to obtain a diammonium hydrogen phosphate solution.

[0052] Steps S2-S6 in Example 1 are the same as steps S2-S6 in Example 1, and the hydroxyapatite (HAP) catalyst is finally obtained.

[0053] Experimental Example 1 Crystal Structure: Cobalt uniform lattice doping, without disrupting the HAP main framework.

[0054] (1) XRD Result Analysis: The products obtained in Examples 1-5 and Comparative Example 1 were subjected to XRD analysis, such as... Figure 1 As shown, pure HAP exhibits a series of sharp characteristic diffraction peaks at 2θ = 25.9°, 31.8°, 32.9°, 34.1°, 39.8°, 46.7°, and 49.5°, which are attributed to the (002), (211), (112), (300), (310), (222), and (213) crystal planes of the HAP crystal, respectively, proving that the method successfully synthesized highly crystalline hydroxyapatite. After cobalt doping, the diffraction peak intensity of 6% Co-HAP decreased slightly, but the peak position remained unchanged, and the structure remained intact, indicating that cobalt species may have entered the HAP lattice in a highly dispersed form. However, as the cobalt doping amount increased to 8% and 10%, the characteristic diffraction peak intensity decreased significantly, the peak shape broadened significantly, and no independent cobalt-based phase diffraction peaks were detected, indicating that excessive cobalt doping easily destroys the long-range order of the HAP framework and reduces the crystallinity of the material, but cobalt mainly exists in the HAP lattice in the form of dopant and does not form a separate phase.

[0055] (2) FTIR analysis: The products obtained in Examples 1-5 and Comparative Example 1 were subjected to FTIR analysis, such as... Figure 2 As shown, pure HAP at 1035, 609, and 565 cm⁻¹ -1 Sharp PO4 appears 3- Characteristic absorptions, corresponding to PO, PO / Ca-O, and Ca-O vibrations respectively, confirm the successful preparation of highly crystalline HAP. The infrared spectrum of the 6% Co-doped sample is almost identical to that of pure HAP, indicating that a small amount of Co is highly dispersed in the lattice and does not disrupt the main structure, but the 565 cm⁻¹... -1 The decrease in peak intensity without significant change in peak position may be due to Co bonding with lattice oxygen and embedding into the lattice, with only a slight decrease in local lattice order. At 8% and 10% high doping, the characteristic peak intensity of phosphate drops sharply, the peak shape broadens, and there are no characteristic peaks of impurity phases. Excessive Co reduces the crystallinity of HAP, but it is still mainly lattice doped and no cobalt-based impurity phases are generated.

[0056] (3) XPS analysis: The products obtained in Example 1 and Comparative Example 1 were subjected to XPS analysis, such as... Figure 3 As shown, Figure 3 a is the XPS full spectrum of the catalytic material. Figure 3 b shows the high-resolution XPS spectrum of Co 2p in the Co-HAP sample. The peaks at 781.6 eV and 797.25 eV are attributed to Co 2p3 / 2 and Co 2p1 / 2, respectively, accompanied by satellite peaks at 786.3 eV and 803.0 eV. The binding energy positions and characteristic satellite peaks indicate that Co mainly exists in the form of Co²⁺, further confirming that Co has been successfully doped into the HAP lattice or loaded on the surface. Figure 3 c represents the high-resolution XPS spectrum of the P 2p of the catalytic material. In HAP, the P 2p3 / 2 and P 2p1 / 2 peaks are located at 132.9 eV and 133.75 eV, respectively. In Co-HAP, the P 2p3 / 2 peak shifts to 133.1 eV and the peak shape broadens, indicating that Co doping alters the chemical environment around P. Figure 3 d represents the O 1s high-resolution XPS spectrum of the catalytic material. Both HAP and Co-HAP show a characteristic peak of lattice oxygen (OL) at 531.1 eV. In addition, an oxygen vacancy / surface adsorbed oxygen (Ov) peak at 533.35 eV was observed in Co-HAP, indicating that the introduction of Co may induce the formation of oxygen vacancies. Figure 3e represents the high-resolution XPS spectrum of the Ca 2p peak of the catalytic material. The Ca 2p3 / 2 and Ca 2p1 / 2 peaks of HAP are located at 347.2 eV and 350.75 eV, respectively. The Ca 2p peak of Co-HAP shows a slight shift towards the direction of higher binding energy (Ca 2p3 / 2 shifts to 347.4 eV), which further proves that the Co ion interacts with the Ca site.

[0057] (4) SEM-Mapping Analysis: The microstructure of pure HAP (Comparative Example 1) and Co-doped HAP (Example 1) was characterized using SEM. For example... Figure 4 As shown, pure HAP ( Figure 4 a) Exhibits obvious particle aggregation characteristics, with a large number of nano-sized HAP grains agglomerating to form micron-sized aggregates. The particle surfaces are rough, and the stacking of grains forms a small number of interstitial pores. The irregularly stacked particle clusters originate from the in-situ self-assembly of calcium ions and phosphate ions and the van der Waals forces between particles during HAP growth. After modification with cobalt ion doping ( Figure 4 b), the overall microstructure of the Co-HAP sample did not change significantly from that of pure HAP, only the density of the aggregates was slightly increased, the surface roughness and the number of pores increased slightly, and a small number of fine new grains were uniformly attached to the surface of the aggregates. (Element Mapping results) Figure 4 c) shows that the distribution of Ca, P and O elements in Co-HAp is highly overlapping, corresponding to the HAP matrix phase. The signal of the doped element Co is completely synchronized with the matrix elements and is uniformly dispersed without local enrichment, confirming that the cobalt element has been successfully and uniformly incorporated into the HAP lattice.

[0058] Experimental Example 2: Free Radical Selectivity: 6% Co-HAP resulted in high-yield ·OH radicals with significant inhibition of secondary free radicals.

[0059] (1) ·OH production: Figure 5 The figures show the changes in hydroxyl radical (·OH) concentration with reaction time in HAP systems with different Co doping ratios. In the pure HAP system, ·OH was almost undetectable within a 6-minute reaction period. After introducing Co doping, the ·OH generation initially increased and then slightly decreased with increasing doping ratio. Among all samples, the 6% Co-HAP consistently exhibited the highest ·OH production, reaching approximately 0.89 mM at 6 minutes, significantly higher than the 2%, 4%, 8%, and 10% Co-HAP components. This demonstrates that the 6% Co doped catalyst exhibits the best performance in activating hydroxyl radical production.

[0060] (2)·O2 - Byproducts: Figure 6 Superoxide radical (·O2) -Quantitative detection curves showed that all Co-doped samples rapidly reached O2 within 1 min of reaction. - The concentration peaked and then gradually decreased. The peak O2 concentrations of 4% and 10% Co-HAP were [not specified]. - Concentrations can reach above 0.06 mM, while 6% Co-HAP has a total O2 content of [missing information]. - The amount generated was the lowest among all groups, with a peak concentration of only about 0.03 mM. The byproduct O2... - The generation of [something] was significantly suppressed.

[0061] (3)·SO4 2- generate: Figure 7 Quantification of sulfate radicals (·SO4) using benzoic acid probe method 2- The characteristic substrate residual concentration curves are used, with the C / C ratio representing the remaining proportion of benzoic acid. Throughout the reaction, benzoic acid underwent almost no oxidation, indicating that the system contained minimal SO42-. 2- The amount generated is extremely low, making it difficult to oxidize benzoic acid probe molecules. Based on the combined quantitative data from three sets of free radicals, it can be concluded that 6% Co-HAP can efficiently induce the formation of ·OH in the system while significantly inhibiting ·O2. - and SO4 2- The catalyst exhibits the reaction characteristics of selectively and directionally generating hydroxyl radicals, resulting in the generation of two types of free radicals.

[0062] Experimental Example 3: Catalytic activity superior to existing mainstream catalysts

[0063] Figure 8 A comparison of normalized specific activities for the generation of hydroxyl radicals (·OH) from PMS by different catalyst systems. As shown in the figure, the normalized specific activity of the Co-HAP of this invention reaches 0.1472 mmol·g. -1 ·min -1 Among all the catalysts compared, it ranks highest. Its specific activity is about 18% higher than Cu-SAC (0.1250), which ranks second, and 84% higher than traditional Fe3O4 (0.0800). It is also higher than other catalysts (such as PI-N, Fe5Mn1C / CN, ZVI, Co9S8@NSBOC, BF). 1.5 The efficiency of the Co-HAP catalyst is 1-2 orders of magnitude higher than that of the R-OVs-Bi4O5I2 catalyst. This result demonstrates that the Co-HAP of this invention achieves highly efficient PMS activation for ·OH production with extremely low dosage (0.1 g / L) and extremely short reaction time (6 min). Its catalytic efficiency per unit mass is significantly superior to many previously reported advanced oxidation catalysts, fully demonstrating the outstanding progress and practical value of the Co-HAP catalyst in hydroxyl radical generation efficiency.

[0064] Example 4: The structure and morphology remained intact before and after the reaction, and the product was stable during long-term use.

[0065] (1) Crystal phase / chemical bond: In order to further verify the physicochemical stability of the catalyst before and after the advanced oxidation reaction from the perspective of phase structure and chemical bond configuration, the present invention used XRD and FTIR to characterize and compare the Co-HAP catalyst before and after the reaction (labeled as Co-HAP and Co-HAP-After, respectively). The results are as follows: Figure 9 As shown. Figure 9 As shown in Figure a, the Co-HAP-After sample, after undergoing the cyclic reaction, still exhibits the characteristic diffraction peaks of highly crystalline hydroxyapatite. The position of its main characteristic peak is completely consistent with that before the reaction, and no independent crystal plane diffraction peaks belonging to cobalt oxide or other metal impurities were detected, indicating that the main framework lattice of the material was not destroyed or reconstructed under the scouring of the strong oxidation reaction system. Meanwhile, as shown in Figure a... Figure 9 The infrared spectrum of b shows that the samples before and after the reaction are at 1035 cm⁻¹. -1 609 cm -1 and 565 cm -1 PO4 at the location 3- The typical characteristic absorption peaks and lattice vibration peaks are intact, with no obvious shift or dissimilarity in peak position, indicating that the main framework functional groups and chemical bonding states on the surface maintain excellent chemical stability during PMS activation. The combined XRD and FTIR results clearly confirm that although the slight activity decay in the aforementioned cyclic tests was caused by the minor dissolution of a small number of active sites on the surface, the overall crystal phase, long-range ordered structure, and main chemical bond network of the Co-HAP catalyst did not undergo any fundamental changes before and after the advanced oxidation reaction. It exhibits excellent and stable lattice and phase stability, fully meeting the stringent quality requirements for structural safety and non-degradation in biomedical catalytic materials.

[0066] (2) Microstructure: To further verify the morphological stability and anti-agglomeration and exfoliation ability of the material from the perspective of microstructure, the Co-HAP catalyst after undergoing 5 advanced oxidation cycles was characterized by SEM. The results are as follows: Figure 10 As shown in the figure, it is clear from the image that after multiple rounds of strong oxidizing free radical scouring and liquid-phase magnetic stirring, the catalyst still maintains its original typical coral-like stacked microstructure formed by the aggregation of micro and nanoparticles and in-situ self-assembly. Figure 4Compared to the microstructure before the reaction in step b, the porosity network between nanocrystals was well preserved. The rough micro / nano surface and loose porous structure did not exhibit any significant collapse, large-area grain melting and agglomeration, or macroscopic matrix peeling. This result strongly demonstrates that the catalyst not only maintains stability at the crystal phase and chemical bond levels but also possesses extremely strong erosion and corrosion resistance at the micro / nano scale morphological framework. This ensures that the active surface can be persistently exposed in complex flow or stirred reaction systems without structural breakage or degradation, exhibiting excellent engineering application potential and long-term safety.

[0067] Furthermore, this material possesses the above structural features, making it particularly suitable for applications in biomedical settings.

[0068] (1) Spatial confinement of free radicals: The HAP matrix is ​​made of micro and nano particles. The short-lived ·OH free radicals generated by catalysis are confined to the micro and nano regions on the surface of the material, which is conducive to the spatial localization of oxidation and reduces non-specific damage to surrounding normal tissues, meeting the needs of precise medical intervention.

[0069] (2) Osteointegration of the substrate: HAP itself has excellent osteoconductivity and protein adsorption capacity. The material of the present invention retains the biological characteristics of the HAP matrix while performing catalytic function, and has the potential to construct a dual-function medical composite material of "in-situ catalysis-osteogenesis".

[0070] The catalyst exhibits high selectivity for generating ·OH during PMS activation, and ·OH is recognized as having broad-spectrum and highly efficient microbial inactivation properties. The catalyst provided by this invention can be used as a functional component for coating modification of the surface of orthopedic implants (such as artificial joints, intervertebral fusion devices, and bone screws), or for composite modification of scaffold materials for repairing infected bone defects, in order to achieve subsequent localized advanced oxidative antibacterial functions.

[0071] The detection method used in this invention is as follows:

[0072] (1) Quantitative detection of ·OH

[0073] Step 1: Accurately weigh 10 mg of the prepared catalyst at room temperature, add 3 mL of deionized water and sonicate until the catalyst is completely dispersed to obtain a uniform catalyst dispersion for later use.

[0074] Step 2: The experiment was conducted in a 200 mL beaker, with the reaction system volume fixed at 100 mL. 90 mL of deionized water, 10 mL of salicylic acid (SA) stock solution, and 2 mL of PMS solution were added sequentially to the beaker to prepare a reaction system with an SA concentration of 0.2 mmol / L. The pH of the system was adjusted to 7-8 using dilute sodium hydroxide solution, and the system was continuously stabilized by magnetic stirring.

[0075] Step 3: Prepare several 5 mL centrifuge tubes in advance, and add 80 μL of sodium thiosulfate solution to each centrifuge tube as a reaction terminator for later use.

[0076] Step 4: Quickly add the pretreated catalyst dispersion to the prepared reaction system and start the reaction timer. Starting from the start of the reaction, take samples at six preset time points: 1 min, 2 min, 3 min, 4 min, 5 min, and 6 min. Each time, use a syringe to draw 4 mL of the reaction solution and quickly transfer it through the filter into a centrifuge tube pre-filled with 80 μL of sodium thiosulfate terminator to quench the active free radicals in the system and terminate the reaction. A total of 6 sets of samples were collected for testing.

[0077] Step 5: Use an ultraviolet spectrophotometer to measure the absorbance of the sample at a detection wavelength of 330 nm, and analyze the concentration of hydroxyl radicals in the system based on the measured absorbance data.

[0078] (2)·O2 - Quantitative detection

[0079] Step 1: Accurately weigh 10 mg of the prepared catalyst at room temperature, add 1 mL of deionized water and sonicate until the catalyst is completely dispersed to obtain a uniform catalyst dispersion for later use.

[0080] Step 2: The experiment was conducted in a 200 mL beaker, with the reaction system volume fixed at 100 mL. 95 mL of deionized water, 1 mL of NBT stock solution, and 2 mL of PMS solution were added sequentially to the beaker to prepare a reaction system with an NBT concentration of 0.05 mM. The pH of the system was adjusted to 7-8 using dilute sodium hydroxide solution, and the system was continuously stirred magnetically to stabilize it.

[0081] Step 3: Prepare several 5 mL centrifuge tubes in advance, and add 80 μL of sodium thiosulfate solution to each centrifuge tube as a reaction terminator for later use.

[0082] Step 4: Quickly add the pretreated catalyst dispersion to the prepared reaction system and start the reaction timer. Take samples at preset time points of 0 min (initial reaction), 1 min, 2 min, 3 min, 4 min, and 5 min. Each time, use a syringe to draw 4 mL of reaction solution, filter it through a syringe filter, and quickly inject it into a centrifuge tube pre-filled with 80 μL of sodium thiosulfate terminator to quench the active free radicals in the system and terminate the reaction. A total of 6 sets of test samples were collected.

[0083] Step 5: After the sample is processed, the absorbance is measured at a detection wavelength of 259 nm using an ultraviolet spectrophotometer. The concentration of superoxide radicals in the system is analyzed in combination with the measured absorbance data.

[0084] (3)·SO4 - Quantitative detection

[0085] Step 1: Accurately weigh 10 mg of the prepared catalyst at room temperature, add 3 mL of deionized water and sonicate until the catalyst is completely dispersed to obtain a uniform catalyst dispersion for later use.

[0086] Step 2: The experiment was conducted in a 200 mL beaker, with the reaction system volume fixed at 100 mL. 90 mL of deionized water, 5 mL of benzoic acid (BA) stock solution, and 1 mL of tert-butanol (TBA) solution were added sequentially to the beaker to prepare a reaction system with a BA concentration of 10 μM and a TBA concentration of 10 mM. The pH of the system was adjusted to 7-8 using dilute sodium hydroxide or dilute sulfuric acid solution, and the system was continuously stabilized by magnetic stirring.

[0087] Step 3: Prepare several 5 mL centrifuge tubes in advance, and add 80 μL of sodium thiosulfate solution to each centrifuge tube as a reaction terminator for later use.

[0088] Step 4: Quickly add the pretreated catalyst dispersion to the prepared reaction system and start the reaction timer. Take samples at preset time points of 0 min (initial reaction), 1 min, 2 min, 3 min, 4 min, and 5 min. Each time, use a syringe to draw 4 mL of reaction solution, filter it through a syringe filter, and quickly inject it into a centrifuge tube pre-filled with 80 μL of sodium thiosulfate terminator to quench the active free radicals in the system and terminate the reaction. A total of 6 sets of test samples were collected.

[0089] Step 5: After processing, the sample was analyzed using high-performance liquid chromatography (HPLC). Detection conditions: mobile phase: water (pH=3, adjusted with phosphoric acid):methanol = 55:45 (v / v), flow rate: 1.0 mL / min, detection wavelength: 227 nm. The concentration of sulfate radicals in the system was analyzed based on the detection data.

[0090] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or basic characteristics. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0091] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a cobalt-doped hydroxyapatite catalyst, characterized in that, Includes the following steps: S1: Preparation of calcium salt solution Calcium nitrate tetrahydrate is dissolved in deionized water, and cobalt chloride hexahydrate is added and dissolved to obtain a calcium-cobalt mixed salt solution; diammonium hydrogen phosphate aqueous solution is prepared. S2: Adjust the pH of the calcium-cobalt mixed salt solution to 10-11 using ammonium hydroxide; S3: Under stirring conditions, add diammonium hydrogen phosphate aqueous solution dropwise to the system obtained in step S2, controlling the Ca / P molar ratio to 1.67, to obtain a reaction suspension; S4: The suspension is placed in a 90 ℃ water bath and stirred for 2 h to crystallize, and then aged at room temperature for 12 h; S5: The aged mixture is filtered, washed, dried at 100 ℃ and ground into powder; S6: The powder is placed in a muffle furnace, heated to 500 ℃ at 2 ℃ / min and calcined for 5 h, then cooled, washed with water and dried to obtain the Co-HAP catalyst.

2. The method for preparing a cobalt-doped hydroxyapatite catalyst as described in claim 1, characterized in that, Step S1 is as follows: Weigh 1.19 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and dissolve it in 100 mL of deionized water, sonicate until the solid is completely dissolved to obtain a calcium nitrate solution; then weigh cobalt chloride hexahydrate according to the target doping stoichiometric ratio, add it to the calcium nitrate solution, stir until completely dissolved to obtain a calcium-cobalt mixed salt solution; separately weigh 0.4 g of diammonium hydrogen phosphate and dissolve it in 100 mL of deionized water, sonicate until the solid is completely dissolved to obtain a diammonium hydrogen phosphate solution.

3. The method for preparing a cobalt-doped hydroxyapatite catalyst as described in claim 2, characterized in that, Step S2 specifically involves adding 0.025 mol·mL⁻¹ dropwise to the calcium-cobalt mixed salt solution. -1 Ammonium hydroxide solution, adjust the pH of the system to 10-11.

4. The method for preparing a cobalt-doped hydroxyapatite catalyst as described in claim 3, characterized in that, Step S3 specifically involves setting the stirring speed to 400 rpm and, under continuous stirring, adding 100 mL of the diammonium hydrogen phosphate solution dropwise to the system obtained in step S2, adjusting the raw material Ca / P molar ratio to 1.67, and obtaining a reaction suspension after the addition is complete.

5. The method for preparing a cobalt-doped hydroxyapatite catalyst as described in claim 4, characterized in that, Step S4 specifically involves placing the suspension in a 90°C water bath and stirring continuously at a constant temperature for 2 hours. After that, the heating and stirring devices are turned off, and the suspension is allowed to stand at room temperature for 12 hours to age.

6. The method for preparing a cobalt-doped hydroxyapatite catalyst as described in claim 5, characterized in that, Step S5 specifically involves filtering and washing the aged mixture, drying the filter cake in an electric oven at 100°C, and then grinding the dried solid into powder.

7. The method for preparing a cobalt-doped hydroxyapatite catalyst as described in claim 6, characterized in that, Step S6 specifically involves placing the powder in a muffle furnace and heating it to 500 °C at a rate of 2 °C / min, then calcining it at a constant temperature for 5 h. After cooling the calcined product, it is filtered and washed again, and the resulting solid is dried at 80 °C to finally obtain the Co-HAP catalyst.

8. A cobalt-doped hydroxyapatite catalyst prepared by the method according to any one of claims 1-7, characterized in that, Hydroxyapatite Ca 10 (PO4)6(OH)2 is the matrix, Co 2+ Ca is replaced by lattice ion substitution. 2+ Uniform doping at each site, with a cobalt doping amount of 2%-10%.

9. The application of the cobalt-doped hydroxyapatite catalyst as described in claim 8 in the selective generation of hydroxyl radicals by activating PMS.

10. The application of the cobalt-doped hydroxyapatite catalyst as described in claim 9, characterized in that, Applications include antibacterial coatings on orthopedic implants, scaffolds for repairing infected bone defects, and oxidative sterilization of medical device surfaces.